Clinical genome editing to treat sickle cell disease—A brief update - Zarghamian, Parinaz; Klermund, Julia; Cathomen, Toni (Frontiers in Medicine, 2023)
Sickle cell disease (SCD) is one of the most common hemoglobinopathies. Due to its high prevalence, with about 20 million affected individuals worldwide, the development of novel effective treatments is highly warranted. While transplantation of allogeneic hematopoietic stem cells is the standard curative treatment approach, a variety of gene transfer and genome editing strategies have demonstrated their potential to provide a prospective cure for SCD patients. Several stratagems employing CRISPR-Cas nucleases or base editors aim at reactivation of γ-globin expression to replace the faulty β-globin chain. The fetal hemoglobin (HbF), consisting of two α-globin and two γ-globin chains, can compensate for defective adult hemoglobin (HbA) and reverse the sickling of hemoglobin-S (HbS). Both disruption of cis-regulatory elements that are involved in inhibiting γ-globin expression, such as BCL11A or LRF binding sites in the γ-globin gene promoters (HBG1/2), or the lineage-specific disruption of BCL11A to reduce its expression in human erythroblasts, have been demonstrated to reestablish HbF expression. Alternatively, the point mutation in the HBB gene has been corrected using homology-directed repair (HDR)-based methodologies. In general, genome editing has shown promising results not only in preclinical animal models but also in clinical trials, both in terms of efficacy and safety. This review provides a brief update on the recent clinical advances in the genome editing space to offer cure for SCD patients, discusses open questions with regard to off-target effects induced by the employed genome editors, and gives an outlook of forthcoming developments.